2018
DOI: 10.3390/nu10101505
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Excess Body Weight-Related Behaviors in a Sample of Brazilian Adolescents

Abstract: The aim of the study was to identify the existence of clusters in multiple lifestyle behaviors, including consumption of fruits/vegetables, sugary products/soft drinks, physical activity and sedentary behavior. The association between identified clusters and excess body weight in a sample of adolescents from Dourados, Brazil, was examined. This is a cross-sectional school-based study involving 578 participants aged 12–18 of both sexes. Anthropometric measurements were performed and a questionnaire was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(44 citation statements)
references
References 28 publications
1
43
0
Order By: Relevance
“…With regard to sedentary and nutritional habits and despite the fact that 74⋅4 % of the participants in our studies performed <3 h of physical activity per week, no statistically significant differences were found in the nutritional status of the patients. This is a finding that is consistent with the one reported by Smetanina et al in Lithuania ( 18 ) , but it is different from what was reported in Brazil ( 25 , 36 , 37 ) , Mexico ( 38 ) , Australia ( 39 ) , Egypt ( 40 ) , Nigeria ( 33 ) , Nepal ( 31 ) , Iran ( 41 ) and among others ( 23 , 42 ) . The relationship between the educational level of the parents and the nutritional status of the children continues to be contradictory, because some studies have reported higher frequencies of overweight or obesity in children whose parents have a higher educational level ( 25 , 31 , 35 , 43 ) , yet, other studies associate less education with higher rates of overweight/obesity ( 18 ) .…”
Section: Discussionsupporting
confidence: 84%
“…With regard to sedentary and nutritional habits and despite the fact that 74⋅4 % of the participants in our studies performed <3 h of physical activity per week, no statistically significant differences were found in the nutritional status of the patients. This is a finding that is consistent with the one reported by Smetanina et al in Lithuania ( 18 ) , but it is different from what was reported in Brazil ( 25 , 36 , 37 ) , Mexico ( 38 ) , Australia ( 39 ) , Egypt ( 40 ) , Nigeria ( 33 ) , Nepal ( 31 ) , Iran ( 41 ) and among others ( 23 , 42 ) . The relationship between the educational level of the parents and the nutritional status of the children continues to be contradictory, because some studies have reported higher frequencies of overweight or obesity in children whose parents have a higher educational level ( 25 , 31 , 35 , 43 ) , yet, other studies associate less education with higher rates of overweight/obesity ( 18 ) .…”
Section: Discussionsupporting
confidence: 84%
“…The studies were developed in 29 different countries, the majority were carried out in USA (n = 6), Brazil (n = 6), and Australia (n = 4), and five [6,11,34,35,50] provided data from more than one country. Regarding country income, 35 studies [11,[23][24][25][26][27]29,30,[32][33][34][35][36][37][38]40,[43][44][45][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] were developed in high-income countries, followed by six [31,39,41,42,46,62] in upper middle-income countries, and one [6] involved data on countries with more than one income. The age group ranged from two [50,63] to nineteen…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
“…The age group ranged from two [50,63] to nineteen [13,42] years. Most studies exclusively investigated adolescents (n = 23) [23][24][25][26]28,31,32,34,35,37,[39][40][41][42][45][46][47][48]55,57,59,60,62], nine [6,29,30,33,38,43,49,51,54] both children and adolescents, and seven (n = 7) [11,44,50,52,53,58,61] only children. In three studies [27,36,56], the sample was composed of children/adolescents but did not report the age group.…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
See 2 more Smart Citations